Optimized Suitable Propagation Model for GSM 900 Path Loss Prediction - Syahfrizal Tahcfulloh; Eka Riskayadi (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
This paper present how COST-231 Hata model is chosen and optimizedfor path loss prediction in suburban area of Tarakan, Indonesia in the GSM 900 MHz system.Thispredicted and optimized path loss model is based on the empirical measurement collected in the GSM system on Tarakan City. It is developed by comparing the calculatedpath loss from collected measurements with the well-known path loss models within applicable frequency range of GSM system, such as COST-231 Hata, Ericsson, SUI, Walfish, ECC-33, and Lee Model. The COST-231 Hata model was chosen based on the closest and smallest mean error ascompared to the measured path loss. This optimized COST-231 Hata model is implemented in the path loss predictionduring the validation process. Thus, this optimized model is successfully improved and would be more reliableto be applied in the TarakanGSM900 MHz system for path loss prediction. DOI: http://dx.doi.org/10.11591/telkomnika.v14i1.7470